Addiction, attachment, and the brain: a focused review of empirical findings and future directions - Unterrainer, Human-Friedrich (Frontiers in Human Neuroscience, 2025)
This focused review integrates theoretical and empirical work from developmental neuroscience, attachment theory, and psychodynamic psychotherapy to reconceptualize addiction as a disorder rooted in disrupted attachment and altered brain function. Drawing on both clinical and research findings, it explores how early relational trauma contributes to dysregulation of stress-response systems and functional changes in brain regions involved in self-awareness, emotion regulation, and reward processing. Particular attention is given to the insular cortex and its role in interoception as it relates to addictive behavior. EEG neurofeedback is introduced as an emerging therapeutic tool, illustrated through a clinical case study that demonstrates how its combination with psychodynamic therapy can foster both neurophysiological regulation and emotional insight. This work supports a view of addiction as a disconnection from bodily and relational signals, rooted in early attachment experiences, and contributes to a more integrative, developmentally informed treatment model.